Upaya Penumbuhan Kecerdasan Spiritual Siswa di Sekolah Dasar Terpadu Putra Harapan Purwokerto - Muh. Luqman Arifin; Sutriyono (Institut Agama Islam Negeri Kediri, 2019)
Abstract: Putra Harapan Integrated Elementary School is one of the schools that establishes the students’ high competence, namely the ability to memorize the Qur’an and hadith of the Prophet, Arabic linguistics and English, leadership, and the operation of MS Word and Excel. The purpose of this study was to reveal the efforts of Putra Harapan Purwokerto’s Integrated Elementary School in instilling students’ spiritual intelligence, by looking at programs carried out through curricular and extra-curricular programs, as well as habituation. The result is first, the teacher acts as a direct role model. Second, the teacher helps formulate the ideals of the students by giving students the task of making targets and promises to be achieved. Third, refraction of worship, prayer, and reading the Qur’an together. Fourth, the teacher tells the story of great figures. Fifth, the teacher uses a religious perspective in solving problems. Sixth, the teacher instills the belief that Allah is Seeing, Seventh, an out door study program, which invites students to visit the orphanage. This study uses a qualitative approach with descriptive data analysis techniques. Abstrak: SD Terpadu Putra Harapan merupakan salah satu sekolah yang menetapkan kompetensi tinggi siswa ajarnya, yaitu kemampuan hafal Al-Qur'an dan hadist Nabi saw., linguistic Arab dan Inggris, leadership, dan pengoperasian MS Word dan Excel. Tujuan penelitian ini adalah mengungkap upaya SD Terpadu Putra Harapan Purwokerto dalam menanamkan kecerdasan spiritual siswa, dengan melihat program yang dijalankan melalui program kurikuler dan ekstra kurikuler, serta pembiasaan. Hasilnya adalah pertama, guru bertindak sebagai teladan langsung. Kedua, guru membantu merumuskan cita-cita siswanya dengan memberikan tugas kepada siswanya untuk membuat target dan janji yang akan dicapai. Ketiga, pembiasan ibadah, berdoa, dan membaca Al-Quran bersama. Keempat, guru menceritakan kisah tokoh-tokoh agung. Kelima, guru menggunakan perspektif agama dalam penyelesaian masalah, Keenam, guru menanamkan keyakinan bahwa Allah Maha Melihat, Ketujuh, program out door study, yaitu mengajak siswa mengunjungi panti asuhan. Penelitian ini menggunakan pendekatan kualitatif dengan teknik analisis data deskriptif.